Litter Inputs, but Not Litter Diversity, Maintain Soil Processes in Degraded Tropical Forests—A Cross-Continental Comparison - Kerdraon, Deirdre; Drewer, Julia; Chung, Arthur Y. C.; Majalap, Noreen; Slade, Eleanor M.; Bréchet, Laëtitia; Wallwork, Abby; Castro-Trujillo, Biancolini; Sayer, Emma J. (Frontiers in Forests and Global Change, 2020)
Land-use change in tropical forests can reduce biodiversity and ecosystem carbon (C) storage, but although changes in aboveground biomass C in human-modified tropical forests are well documented, patterns in the dynamics and storage of C belowground are less well characterised. To address this, we used a reciprocal litter transplant experiment to assess litter decomposition and soil respiration under distinct litter types in forested or converted habitats in Panama, Central America, and in Sabah, Malaysian Borneo. The converted habitats comprised a large clearing on the Panama Canal and oil palm plantation in Borneo; forested habitats comprised a 60-year old secondary forest in Panama and a disturbed forest in Borneo that was selectively logged until 2008. In each habitat, we installed mesocosms and litterbags with litter collected from old-growth forest, secondary forest or an introduced species: Elaeis guineensis in Borneo and Saccharum spontaneum in Panama. We measured litter mass loss, soil respiration, and soil microbial biomass during nine months at each site. Decomposition differed markedly between habitat types and between forest vs. introduced litter, but the decay rates and properties of old-growth and secondary forest litters in the forest habitats were remarkably similar, even across continents. Slower decomposition of all litter types in the converted habitats was largely explained by microclimate, but the faster decay of introduced litter was linked to lower lignin content compared to the forest litter. Despite marked differences in litter properties and decomposition, there was no effect of litter type on soil respiration or microbial biomass. However, regardless of location, litter type, and differences in soil characteristics, we measured a similar decline in microbial activity and biomass in the absence of litter inputs. Interestingly, whereas microbial biomass and soil respiration increased substantially in response to litter inputs in the forested habitats and the converted habitat in Panama, there was little or no corresponding increase in the converted habitat in Borneo, indicating that soil recovery capacity had declined substantially in oil palm plantations. Overall, our results suggest that litter inputs are essential to preserve key soil processes, but litter diversity may be less important, especially in highly disturbed habitats.